الـرشادة السياسيـة وعلاقتها بالتحول الديمقراطي - نايت سعيدي, إلهام (Sciences humaines, 2014)
قد عرفت عدة مناطق من العالم موجة من التغييرات السياسية عُرفت بالتحول الديمقراطي، وهو عملية الانتقال من أنظمة تسلطية إلى أنظمة ديمقراطية، ولتحقيق ذلك لابد من ترشيد السلطة للوصول إلى الرشادة السياسية بإقرار الشفافية والمحاسبية. والدعوة إلى إنشاء دولة القانون وإعادة تفعيل المجتمع المدنين وهذا لن يكون إلا عن طريق المشاركة السياسية الإيجابية. في هذا الإطار سيحاول هذا المقال تسليط الضوء على الرشادة السياسية وعلاقتها بالتحول الديمقراطي.   Many countries over the world have a large wave of political changes, that has been known as the democratic regime; that is the known process of transition from the authorization regime to democratic one. But to achieve this must rationalization of the authority by the realization the good governance with adopting the transparency and the accountability also with the creation the state society. This will be only with the participation of politic. In this field the easy is an attempt to clarify the good governance and its relationship with the Democratic transition.